Pengaruh Terapi Musik terhadap Tingkat Nyeri Anak Usia Prasekolah Saat Dilakukan Pemasangan Infus - Dewi, Kadek Mira; Purnamayanthi, Pande Putu Indah; Karuniadi, I Gusti Agung Manik (STIKes Hamzar, 2025)
IV infusion is a medical procedure that can cause discomfort, including pain, particularly in children. Children's pain can be quantified using the Wong Baker Faces Rating Scale questionnaire. One treatment option for overcoming this is to provide music therapy during IV infusion. The research design was a pre-experimental with an intact-group comparison design. The sample size was 34 respondents, divided into 17 experimental groups and 17 control groups, and the sampling technique was non-probability sampling, namely purposive sampling. The amount of pain among children in the control group when the infusion was performed in the Cilinaya ward of Mangusada hospital was described as follows: all 17 respondents (100% reported moderate pain). The average pain level among children in the control group was 3.76. In the intervention group, all respondents reported minor pain. Children in the intervention group reported an average pain level of 1.71. The Mann-Whitney statistical test yielded a p-value of 0.000 <0.05, indicating that music therapy affected pain levels in preschool children when administered in the Cilinaya ward.